Long-term follow-up of IPEX syndrome patients after different therapeutic strategies: An international multicenter retrospective study - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (MOSBY-ELSEVIER, 2018)
Background: Immunodysregulation polyendocrinopathy enteropathy x-linked(IPEX) syndrome is a monogenic autoimmune disease caused by FOXP3 mutations. Because it is a rare disease, the natural history and response to treatments, including allogeneic hematopoietic stem cell transplantation (HSCT) and immunosuppression (IS), have not been thoroughly examined. Objective: This analysis sought to evaluate disease onset, progression, and long-term outcome of the 2 main treatments in long-term IPEX survivors. Methods: Clinical histories of 96 patients with a genetically proven IPEX syndrome were collected from 38 institutions worldwide and retrospectively analyzed. To investigate possible factors suitable to predict the outcome, an organ involvement (OI) scoring system was developed. Results: We confirm neonatal onset with enteropathy, type 1 diabetes, and eczema. In addition, we found less common manifestations in delayed onset patients or during disease evolution. There is no correlation between the site of mutation and the disease course or outcome, and the same genotype can present with variable phenotypes. HSCT patients (n = 58) had a median follow-up of 2.7 years (range, 1 week-15 years). Patients receiving chronic IS (n 5 34) had a median follow-up of 4 years (range, 2 months-25 years). The overall survival after HSCT was 73.2% (95% CI, 59.4-83.0) and after IS was 65.1% (95% CI, 62.8-95.8). The pretreatment OI score was the only significant predictor of overall survival after transplant (P = .035) but not under IS. Conclusions: Patients receiving chronic IS were hampered by disease recurrence or complications, impacting long-term.disease-free survival. When performed in patients with a low OI score, HSCT resulted in disease resolution with better quality of life, independent of age, donor source, or conditioning regimen.
Keywords: IPEX; primary immune deficiency; FOXP3; Treg cells; hematopoietic stem cell transplantation; immunosuppression; rapamycin; enteropathy; neonatal diabetes; genetic autoimmunity; X-LINKED SYNDROME; STEM-CELL TRANSPLANTATION; REGULATORY T-CELLS; IMMUNE DYSREGULATION; POLYENDOCRINOPATHY; ENTEROPATHY; IMMUNODYSREGULATION; ENGRAFTMENT; MUTATIONS; SIROLIMUS